2018
DOI: 10.1093/geronb/gby016
|View full text |Cite
|
Sign up to set email alerts
|

Situation-Based Contingencies Underlying Wisdom-Content Manifestations: Examining Intellectual Humility in Daily Life

Abstract: These results offer new directions for research on the expression of wisdom-related characteristics in daily life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 55 publications
0
41
0
Order By: Relevance
“…In another set of studies comparing wise reasoning about several interpersonal situations on the same participants indicated that stability was also modest when testing responses to the different interpersonal conflicts in the same session, or when examining test-retest stability in wise reasoning scores collected from the same participants several years apart (Brienza, Kung, Santos, Bobocel, & Grossmann, 2017a, b). Finally, significant variability was also observed in a recent experience sampling study of intellectual humility (Zachry et al 2018).…”
Section: Cross-situational Variability In Wisdom: Evidence From Obsermentioning
confidence: 67%
“…In another set of studies comparing wise reasoning about several interpersonal situations on the same participants indicated that stability was also modest when testing responses to the different interpersonal conflicts in the same session, or when examining test-retest stability in wise reasoning scores collected from the same participants several years apart (Brienza, Kung, Santos, Bobocel, & Grossmann, 2017a, b). Finally, significant variability was also observed in a recent experience sampling study of intellectual humility (Zachry et al 2018).…”
Section: Cross-situational Variability In Wisdom: Evidence From Obsermentioning
confidence: 67%
“…Intensive longitudinal methods (e.g., capturing states of Openness throughout the day) such as experience sampling may help characterize shorter momentary states and address potential biases in recall that can affect even brief daily time frames (Shiffmann, Stone, & Hufford, ). In addition, it may also be fruitful to examine momentary Openness as enacted in relevant and specific types of situations (e.g., interpersonal conflict, exposure to new situations), a method already used to study other momentary personality states (e.g., Grossmann, Gerlach, & Denissen, ; Zachry, Phan, Blackie, & Jayawickreme, ). Second, the generalizability of these findings is also restricted by the present sample’s limited ethnoracial diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Like self-esteem, IH can be seen as a trait that varies from one individual to another, i.e., in general, how intellectually humble an individual is in different situations and at different times. It also can be seen as a state that changes within persons, i.e., how intellectually humble an individual is in a specific situation or at a specific time (Zachry et al, 2018). Therefore, we can conclude that IH is constant to some extent but may change at a given time due to internal or external factors.…”
Section: Definition and Characteristicsmentioning
confidence: 93%
“…Relationships between the general IH and several kinds of specific IH (e.g., politics, religion, and education, et al) were also investigated using these two scales, and only slight correlations were found. Zachry et al (2018) distinguished between trait IH and state IH and developed a scale to measure them by only changing verb tense (e.g., for trait IH: "I view the challenging of my ideas as an opportunity to grow and learn" & for state IH: "I viewed the challenging of my ideas as an opportunity to grow and learn"). This scale has been proven to have only one factor and good convergent and discriminant validity.…”
Section: Measurementmentioning
confidence: 99%